Diseño de una metodología de integración de Gestión de Conocimiento en la práctica de Gerencia de Proyectos de la oficina de proyectos de una empresa de servicios de Bogotá - basada en el estándar del Project Management Institute (PMI) (2017)
Knowledge management on the one hand, and project management on the other, are areas that during the last decades have had significant development for organizations in all economic sectors and types of industry in which they perform. For this reason, this degree work aims to provide a characterization from the theoretical point of view of these two areas of knowledge and on the concept convergence from theoretical and empirical approaches; With the purpose of proposing a methodology of integration of knowledge management in the practice of project management in the project office of a service company in Bogotá, in the components: knowledge management model, knowledge management processes, Roles and responsibilities, tools and schemes for management and measurement of knowledge assets; In order to promote the achievement of strategic results for the organization and construction of potential sustainable competitive advantages.